The Roles of Information Technology in Islamic Bank Knowledge Management: A study of Two Syariah Banks in Palu - Nurdin, Nurdin (State Institute of Islamic Studies (IAIN) Palu, 2016)
Information technology has been considered as a vital tool for modern organizations to support their knowledge management projects. Previous studies have found that success knowledge management projects were supported by various information technology infrastructures. They addressed how information technology has succesfully implemented to support knowledge management project within conventional banks. However, limited study has been proposed regarding how information technology play roles in support knowledge management project within Islamic banks. Through the case study approach, the author studied the use of information technology for knowledge management process within two Bank Syariah (Bank Mandiri and Bank BNI Syariah) in Palu Central Sulawesi. The author collected data through observation, written material, and in-depth interviews with key informants from both banks. The findings show that information technology infrastructures have played important roles in support knowledge management projects within the Islamic banks. Those information technology infrastructures includes internet, intranet, websites, communication application such as email, and social media. This study sheds light and provides new insight on how information technology has succesfully used to support knowledge management within Islamic banks. The results benefits both academic and practioners in Islamic banks and knowledge managemet area. As the social media was an important finding for knowledge management in Islamic banks, future research need to focus on how social media should be used for knowledge management projects in Islamic banks